THE METHOD OF USING THE INFORMATION EDUCATIONAL ENVIRONMENT IN THE DEVELOPMENT OF STUDENTS' SPIRITUALITY (American Journal of Technology and Applied Sciences, 2023)
The article provides information on the methodology of using the information educational environment in the development of students' spirituality.